The profile and cost of end-of-life care in South Africa - the medical schemes' experience - Botha, Pieter (University of Cape Town, 2020)
South African medical schemes spend billions of Rands each year on medical care costs for their beneficiaries near their end of life. Hospi-centric benefit design, fee-for-service reimbursement arrangements and fragmented, silo-based delivery of care result in high, often unnecessary spending near the end of life. Factors including an ageing population, increasing incidence rates of cancer and other non-communicable diseases, and high levels of multi-morbidity among beneficiaries near their end of life further drive end-of-life care costs. Low levels of hospice or palliative care utilisation, a high proportion of deaths in-hospital and chemotherapy use in the last weeks of life point to potentially poor-quality care near the end of life. The usual care pathway for serious illness near the end of life acts like a funnel into private hospitals. This often entails resource intensive care that includes aggressive care interventions right up until death. The result is potentially sub-optimal care and poor healthcare outcomes for many scheme beneficiaries and their surviving relatives. Understanding the complex nature of the end of life, the different care pathways, the available insurance benefits, the interactions between key stakeholders and the multitude of factors that drive end-of-life care costs are vital to setting end-of-life care reform in motion. In order to increase value at the end of life, i.e. to increase quality and/or to reduce costs, benefit design reform, alternative reimbursement strategies, effective communication and multi-stakeholder buy-in is key.